Antenatal clinics - Cavassa, Nicolás (2015)
The author shows the present organization of Out-Patients Department of the Hospital Maternity of Lima that it has appropriate services as Urological, X-Ray, Dental, laboratory, Social Work, etc. However, should be necessary a best coordination between the Out and In. Patient Departments and the importance to take and apply rules and regulations of one standard organization.